An evidence-based review on quackery in dentistry - Shail Kumari; Sunil Kumar Mishra; Pankaj Mishra (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Uncustomary medicine has been known since ancient period and is very commonly practiced by many individuals. Due to traditions and religious beliefs, these different unconventional practices were followed in the form of quackery. PURPOSE: This review is done to focus the quack practices done in dentistry affecting the oral health of the individuals and what measures to be taken to totally eradicate it from the society. MATERIALS AND METHODS: In April 2018, an electronic data search was done to find the published literature in PubMed, Medline, and EBSCOhost database. The search was focused on reports on quack practices in dentistry, reason behind such practices and their effects on oral health of the individuals. The titles and abstracts obtained in relation to focused questions were screened. Handsearching of other printed articles was also performed. The articles published in only English language were considered for the study. RESULTS: The initial search resulted in 102 papers. The abstracts of the articles related to the focus question were independently screened by the reviewers. Eighty-seven articles were excluded for not being related to topic or not in English or whose abstract is not available. Handsearching of literature resulted in one additional paper. A total of 16 articles were included in the review, of which five articles reported dental treatment of subjects poorly treated with quacks and one article is on patient's perception toward dental quacks. CONCLUSION: Quackery in dental field is growing fast in cities and villages and it is going to be a major challenge to populations due to unsterilized instruments being used. This gives unethical practices, giving invitation to certain major health hazards in the form of AIDS and hepatitis to individuals. It is the major responsibility of the government organizations and dental councils to interfere in the current scenario, so that quack practices in dental field can be eliminated from its roots, and to provide good oral treatment and education to the population who are in real need of it.